INSIGHT FROM THE ACTIVE SITE PREDICTION OF THE HUMAN RAC-ALPHA SERINE/THREONINE PROTEIN KINASE MODEL. - VIDYANATH CHAUDHARY; SHAKILA AFROZ; KAILASH SINGH; VINEET KUMAR MISHRA (International Journal of Pharma and Bio Sciences, 2013)
RAC-alpha serine/threonine-protein kinase is an enzyme encoded by AKT1 gene in human. The activation inhibits the phenomenon of apoptosis, one of the major causes for promoting cancer. In experiment with mice lacking Akt1, they become resistant to cancer. There is no sufficient information regarding RAC-alpha serine/threonine-protein kinase in Homo sapiens. Therefore, we describe the development of RAC-alpha serine/threonine-protein kinase model in human. We further document the predicted active sites in the structural model with solvent exposed ASA residues. During this study, the model was built by CPH program and validated through PROCHECK, Verify 3D, ERRAT and ProSA for reliability. The active sites were predicted in the model with further ASA analysis of active site residues. The discussed information thus provides insight to the predicted active site of RAC-alpha serine/threonine-protein kinase in human.